Metodologia para quantificação de gastos públicos no combate a incêndios florestais em unidades de conservação - Silva, Elaine Cristina Gomes da (2017)
Forest fires have increased considerably in recent years and are considered one of the main environmental issues faced by the management units of Conservation Units nowadays. Although fire is part of the natural process of managing some ecosystems, its frequency and intensity, as it has been occurring due to climate change, causes several damages to nature. In addition to these factors, the lack of public resources, records and effective criteria established for the execution of forest fire prevention and control activities has been a major challenge in the management of public expenditures for the preservation of forests. Thus, the premise of this work is based on the proposal of a tool whose objective is to estimate the expenditures incurred by the public sector on the use of resources in forest firefighting. In order to do so, this study, characterized as exploratory, through ex post facto and documentary case studies, used multidisciplinary vires in order to obtain the different expenditures with resources used to combat forest fires, elaborating a method of quantification. The method was elaborated based on the legislation related to the accounting of public expenditures, with the guidance of the Multiple Criteria Decision Making method, to define the criteria for quantification of resources. Descriptive statistics, ANOVA and means test were used with Software R. The proposed method showed consistency in the results obtained between the two case studies, thus achieving the average expenditure of resources per hectare burned, both quantity and value. At the end, it was concluded that the total amount spent with state resources was at least 20% higher than the federal and municipal expenditures for the two case studies and that the highest expenditures per hectare were attributed to the workforce and maintenance of vehicles and aircraft (about 30 to 40% for both) and with fuel (15%). In general, the greatest perceived demands were specialized manpower and specific firefighting equipment.